Teaching locomotion biomechanics: from concepts to applications. (28th January 2019) - Seyfarth, André; Schumacher, Christian
Abstract: Our daily activities involve different types of locomotion, including walking and running. In this paper we present a series of biomechanical models to describe such locomotor activities with a set only a few characteristic parameters. With this we aim at providing an introduction to the modelling of human locomotion which is equally appropriate for high-school and university-level students. We share our experiences with integrating these biomechanical models into classes with students of different disciplines comprising engineering, computer science, physics and sport science. Supplementing these modelling approaches, we use experimental methods as well as robotic testbeds to evaluate and justify the biomechanical simulation models. By this, we enable students from different fields to gain first experiences in the understanding and application of human movement systems and potential extensions to related technologies, such as robotics and assistive devices (e.g. prostheses and exoskeletons).